Patient compliance in assessing electronic patient-reported outcome measures after urologic surgery - Grüne, Britta; Menold, Hanna; Lenhart, Maximilian; Mühlbauer, Julia; Walach, Margarete; Waldbillig, Frank; Neuberger, Manuel; Nuhn, Philipp; Michel, Maurice Stephan; Koenig, Julian; Kriegmair, Maximilian; Wessels, Frederik (Urologia internationalis, 2023)
Introduction: This study aimed to assess patient compliance with a newly established electronic patient-reported outcome measure (ePROM) system after urologic surgery and to identify influencing factors. Methods: Digital surveys were provided to patients undergoing cystectomy, radical or partial nephrectomy, or transurethral resection of bladder tumor via a newly established ePROM system. Participants received a baseline survey preoperatively and several follow-up surveys postoperatively. Multivariable regression analysis was performed to identify factors predicting compliance. Results: Of N = 435 eligible patients, n = 338 completed the baseline survey (78.0%). Patients who did not participate were significantly more likely male (p = 0.004) and older than 70 years (p = 0.005). Overall, 206/337 patients (61.3%) completed the survey at 1-month, 167/312 (53.5%) at 3-month, and 142/276 (51.4%) at 6-month follow-up. Lower baseline quality of life (odds ratio: 2.27; p = 0.004) was a significant predictor for dropout at 1-month follow-up. Low educational level was significantly associated with low compliance at 3- (OR: 1.92; p = 0.01) and 6-month follow-up (OR: 2.88; p < 0.001). Conclusion: Acceptable compliance rates can be achieved with ePROMs following urologic surgery. Several factors influence compliance and should be considered when setting-up ePROM surveys.